Penyidikan Terhadap Tindak Pidana Keterangan Palsu Dalam Akta Otentik Oleh Kepolisian Resort Kota Pekanbaru - Irna Dianis Purba; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
An authentic deed is a deed in the form prescribed by law, be made by or beforepublic officials ruling for it in a place where the deed made pursuant to Article 1868Burgerlijk Wetboek. Officials authorized to make an authentic deed is a Notary, thePresident, ministers, governors, regents, Head, Civil, bailiff, judge and so on. The authenticact is one proof that has the force of law. However, still stout forgery committed by partiesthat may cause harm to the other party. The role of the investigator is very important incriminal cases counterfeiting authentic deeds, and therefore required the implementation ofcriminal investigations in the area of counterfeiting deed City Police Law Pekabaru as statedin Article 266 paragraph (1) of the Criminal Justice Act.This research type is classified in this type of sociological juridical research. Becausein this study the authors directly conduct research on the location or point examined in orderto provide a complete and clear picture of the problems examined, the study was conductedin Pekanbaru City Police. The data used is primary data, secondary data and data tertiary,technical data collection using interviews and literature study.From the results of research and discussion can be concluded that the First, theimplementation of criminal investigations in any jurisdiction in Pekanbaru City Police doesnot run properly. Second, barriers Pekanbaru City Police are searching for evidencepembading, presenting expert witnesses, the detention period of suspects, searching for andfinding an authentic deeds are false, and collect evidence at the crime scene. Third, effortsmade by the police within the constraints of the investigation of criminal perjury in anauthentic deed by City Police Pekanbaru is to coordinate the agencies (Notary, Head, etc.),Searching for resources occurrence of criminal cases of forgery, presenting an expertwitness, gathering evidence, and to disseminate the relevant agencies (Notary, Head, etc.).Advice authors, the implementation activities inquiry City Police Pekanbaru conduct theinvestigation process can immediately resolve the handling of criminal cases ofcounterfeiting authentic act and regulation governing criminal offenses be more specific insetting the rules regarding the criminal act against false information in an authentic deedand obstacles that occur during the implementation process of investigation can be overcomewith efforts that may be made.Keywords: Investigation - Crime - Counterfeit authentic deed